2002
DOI: 10.1046/j.1355-557x.2002.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spectral composition on larval haddock, Melanogrammus aeglefinus L., growth and survival

Abstract: In a small-scale culture experiment, larval haddock, Melanogrammus aeglefinus L., were raised under various combinations of light quality [blue (470 nm), green (530 nm) or full-spectrum white light] and light intensity [low (0.3±0.4 mmol s À1 m À2 ) or high (1.7±1.9 mmol s À1 m À2 )], and in total darkness (both fed, and starved). Larval growth (0.9% day À1 in standard length; 2.4% day À1 in body area) was not significantly different between any combination of coloured light. At the time of total mortality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…However, there-are some exceptions. For instance, the growth rate in some species (Atlantic salmon, haddock) is independent of light wavelength (Stefanson and Hansen 1998;Downing 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there-are some exceptions. For instance, the growth rate in some species (Atlantic salmon, haddock) is independent of light wavelength (Stefanson and Hansen 1998;Downing 2002).…”
Section: Resultsmentioning
confidence: 99%
“…and young carp (Cyprinus carpio L.) increased with green light (Radenko and Alimov 1991;Ruchin et al 2002). Gaignon and co-workers (Gaignon et al 1993) revealed a negative effect of yellow light on Na + , K + -ATPase activity in Atlantic salmon Salmo salar L. However, no difference was detected in the growth rate of Altantic salmon and haddock treated with colored light (Stefansson, Hansen, 1989;Downing, 2002).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Development of haddock aquaculture has occurred mainly in Canada (Downing and Litvak, 1999;Aiken, 2003), where research has been carried out on parental effects and environmental conditions in the hatchery period (Downing and Litvak, 1999Buckley et al, 2000;Downing, 2002;Trippel and Neil, 2003;Rideout et al, 2004a, b), the effects of photothermal manipulation on reproductive development (Martin-Robichaud and Berlinsky, 2004), live and particulate feed requirements (Hamlin and Kling, 2001;Kim and Lall, 2001), and dietary nutrient requirements (Nanton et al, 2001;Lall et al, 2003). However, the on-growing performance of haddock has not received much attention, although fish have been farmed in netpens by Heritage Aquaculture Limited in Canada; up to 50 t of skinless, boneless fillets were marketed and sold in Canada and the USA per annum between 2000 and 2005 (A. S. Lall, pers.…”
Section: Introductionmentioning
confidence: 98%
“…Most species of fish have well-developed color sight, and are therefore very sensitive to colored light. For instant, the survival rate of haddock larvae (Mellanogrammus aeglefinus L.) is higher with blu and green light (Downing 2002). The growth rate of silver carp larvae (Hypophthalmichthys molitrix Val.)…”
Section: Introductionmentioning
confidence: 99%